Evaluasi Kriteria Kesesuaian Lahan Kelapa Sawit di Kebun Baru PT. Perkebunan Nusantara-I, Langsa - Abubakar Karim (Jurnal Agrista, 2008)
Evaluation of Land Suitability Criteria for Oil Palm at Kebun Baru PT. Perkebunan Nusantara-I, LangsaABSTRACT. The obtain land suitability classes in accordance with plant production, the appropriate of land suitability classification from land suitability classification system is required. The aims of this study were: (1) to evaluate the suitability of classification system for land planted with oil palm at Kebun Baru PT. Perkebunan Nusantara I Langsa and (2) to evaluate the relationship between soil characteristics (criteria) and the production of oil palm in the Kebun Baru PT. Perkebunan Nusantara I Langsa. The characteristics observed in the area of land that formed homogenous classes were based on the uniformity of slope, soil type on the rate of oil palm production. From each homogenous area soil samples were taken for analyze of physical and chemical soil properties. The result showed there was none of the system of land suitability classification can be applied directly in Kebun Baru PT. Perkebunan Nusantara I Langsa. A significant correlation was found among the land characteristics and slope was very evident and determined other land characteristics, including the production of oil palm. The oil palm production in Kebun Baru PT. Perkebunan Nusantara-I Langsa was determined by slope, C-organic, P-available, K-exchangeable, Ca-Exchangeable, base saturation, and salinity. The relationship between oil palm production and land characteristics was described as multiple regression: Y = 5,55 – 0,41x1 + 2,77x6 + 0,24x8 + 8,57x9 - 1,96x10 + 0,39x13 – 2,83x14; R2 = 0,93**   x1 = Slope, x6 = C-organic, x8 = P-available, x9 = K-exchangeable, x10 = Ca-exchangeable, x13 = base saturation, x14 = salinity; R = determination value. To achieve the best fit between the classification of land suitability and oil palm production in Kebun Baru PT. Perkebunan Nusantara I Langsa, the modification of land suitability classification system is required.